Preparing learners for higher education success through individualised home education in South Africa: a narrative research study - Morkel, Jacqueline (University of the Free State, 2024)
The South African education system is currently severely criticised for failing to adequately prepare learners for higher education, leading to high dropout rates and unfulfilled potential. Previous research has indicated how this challenge could be addressed through educational reform – on multiple levels of the educational system – and how to support underprepared higher education students to achieve success. However, what is not known is how a home education environment could prepare students for higher education success in the context of a developing country like South Africa. The purpose of this study is to create a deeper understanding of how a specific approach to home education, i.e., individualised home education, could effectively prepare learners for higher education success. As a qualitative research study from an interpretive perspective, this study used narrative inquiry method to achieve the above mentioned purpose. Snowball sampling was utilised to obtain adults who firstly have successfully completed their undergraduate studies at a public South African university, in the minimum residential period allowed for each of the participant’s respective degree programmes. Secondly, it was important that these families applied an individualised home education approach. Semi-structured serial interviews were conducted in order to gather rich and meaningful data. A total of twenty-one interviews were conducted of which fifteen interviews were transcribed. The data presented in this study included the first round interviews of seven home educated adults and five home education parents with two sets of siblings being interviewed. The second round of semi-structured interviews involved seven participants, i.e., four homeschooled students and three parents. A thematic data analysis process was used to analyse the data. The data presented four themes which describe individualised home education pertaining to higher education success: (1) milieu, (2) learning, (3) life skills and (4) quality interactions. The data indicated specific aspects for each of these elements. These aspects created a nuanced understanding of the home education environment that successfully prepared students for higher education success in later years. The research results were then compared with student engagement as a theoretical frameworks for higher education success. This comparison between the research results (at earlier education phases) and student engagement, provided correlations between the data and student engagement mechanisms: Affective-, Behavioural-, Cognitive-, Critical-, Political- and Socio-cultural student engagement. The results showed that individualised home education was highly effective in incorporating student engagement strategies, which was adapted throughout developmental phases, and how this education philosophy successfully prepared learners for higher education success, because it effectively facilitated learner engagement at the Primary and Secondary level. This research study provides deep insights, in an empirically grounded way, about the value of home education – especially individualised home education – and how it could prepare learners for post-secondary success.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2024
Keywords: Home education; Higher education; Individualised education; Higher education success; Student engagement